SYSTEMATIC REVIEW: THE RELATIONSHIP BETWEEN LEAD EXPOSURE IN CHILDREN AND PARENTAL OCCUPATION - Yuliana, Elvida; Suraya, Anna; Jenie, Renan Prasta; Triwibowo, Agung Cahyono; ., Zakiyah; Rahmawati, Apriana (Jurnal Penelitian Kesmasy, 2025)
Lead is a toxic heavy metal and a common occupational and environmental toxin. Lead is used in more than 900 occupations. Lead exposure may produce serious consequences for the health of children. We do meta-analysis articles from PubMed, Google Scholar and Science Direct. We found 24 studies from 14 countries after selected from 1703 countries. Results showed that parental occupations that can increase lead levels include are e-waste worker, fishing net production, lead industry worker, construction, household bullet production, vehicle employee, mining worker, farmer, technician, repair work at home, smelting worker, metal seeker, plumber, battery/lead recycler, laundry-person, artisanal worker, scrap metal cookware production, and jewelry production.